Pengaruh Variasi Gaya Tekan Pada Proses Kompaksi Kampas Rem Dengan Matriks Phenolic Resin - Susilo, Eko, Bambang W. Febriantoko, ST, MT (2016)
Brake is one component of a motor vehicle that serves to slow or stop the vehicle, especially a ground vehicle. Especially when a high-speed vehicle brake function has an important role, even human lives depend on the efficacy of the brake lining material. It would require a special design on the canvas material. The materials used in this study is the aluminum powder, brass powder, Barium Sulfate, Calcium Carbonate, carbon, fiberglass and phenolic resin as a matrix. Manufacture of brake pressed with a press force of 6 tons for 7 minutes at a temperature of 150ºC, in the oven for 60 minutes with a temperature of 200 ° C. The results showed that the friction test (the influence of water and the influence of oil) the degree of wear of brake lining indopart lower than the brake with the variation of the compressive force (6 tons, 7.5 tons and 9 tons). For testing of dry friction brake pressing force 9 tons lower than the wear rate of the brake lining indopart. Then for the coefficient of friction brake highest indopart on dry swipe test, and the influence of oil. Then test the influence of water friction coefficient of friction brake with the highest compressive force variation of 6 tons and 9 tons. In Durometer hardness testing with brake indopart has the highest hardness value that is equal to 94 Shore D, while approaching the hardness value is the brake with the variation of the compressive force of 9 tons, accounting for 92 Shore D.